ANALYSIS OF ORGANIC MATTER CONTENT IN WATER AND SEDIMENT IN THE EAST COAST WATERS OF BENGKALIS ISLAND, RIAU PROVINCE - Lestari, Anggi; Amin, Bintal; Nursyirwani, Nursyirwani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Organic matter is one indicator of environmental fertility both on land and at sea. The content of organic matter in a certain amount can be useful for aquatic biota, but if the amount of organic matter exceeds the assimilation capacity of the waters, it can cause a disturbance. This study aims to determine the organic matter content of water and sediment at high and low tide conditions in the waters of the east coast of Bengkalis Island and to determine the relationship. The method used is a survey method that is carried out in the field directly to collect data and samples, which are then taken to the laboratory for analysis. The results showed that the organic matter content of water at high tide was 17.38-25.28 mg/L and at low tide, it was 29.63-35.55 mg/L. The organic matter content of sediments at high tide conditions ranged from 2.28-5.37% and at low tide, conditions ranged from 3.46-8.62%. These conditions indicate that the organic matter content of water and sediment has not passed the predetermined threshold. The results of the analysis of the relationship between the organic matter content of water and sediment at high tide conditions with a coefficient of determination (R2) of 0.533 with a correlation coefficient (r) of 0.730 and at low tide with a coefficient of determination (R2) of 0.713 with a correlation coefficient (r) of 0.844. The type of sediment that dominates the waters of the East Coast of Bengkalis Island is mud.